Hybrid Parallel Multithreading Encryption - Deepali (International Journal of Computer Sciences and Engineering, 2025)
First part of this thesis which was needed to be developed before moving onto the next levels is Cloud Computing. The client section was a simple application for user which was made on Socket Programming in Java. Application connection is to be made with Server which is a LAN based server on which data is to be uploaded and downloaded. Since backbone network (client and server) is developed, then it needs to be secured with a particular algorithm or technique. The algorithm studied is known as RSA key oriented algorithm which offers dynamic security on client and server level during communication. The other technique for advancing the level of scalability and improvement along the network layer we used is NTRU encryption. Since this algorithm encrypt data of every type ensures the originality of particular data and adds the advancement in throughput level. These two algorithms are implemented to run on single server on a different core thread thus making the idle cores of sever in use for both the algorithms. It is reflecting that the parallelism encryption done on single content during the data storage on network marginally increase the speed of execution and decryption and encryption timings have been increased. Other part of this thesis also deals with the approaches followed previously which are the part this thesis.